Tropical cyclones in Mexico: a comparative analysis and a composite socioeconomic damage index - Castillo Loeza, Diana Estefanía (2025)
Tropical cyclones (TCs) are associated with significant and destructive natural disasters, making the assessment and analysis of the resulting damage essential for effective disaster risk management. The main objectives of this research are to estimate the annual probability of Tropical Cyclones (TCs), analyse four socioeconomic damage variables (fatalities, affected population, damaged houses, and economic losses) related to TCs in Mexico from 1970 to 2023, and construct a composite socioeconomic damage index. Time series analyses were conducted to evaluate the four socioeconomic damage variables extracted from the damage databases. CENAPRED database was selected for a temporal-spatial analysis of cumulative data at the state level, covering the period from 1980 to 2023. A bootstrap PCA analysis was performed to assess the stability of the weights assigned to each variable in the index. At least one hurricane is expected to have socio-economic effects on the national territory each year. Discrepancies in the information from the three databases reveal differences in the reported data and time periods. According to the composite index, states like Guerrero, Veracruz, Oaxaca, and Nuevo León exhibit the highest levels of accumulated damage. However, it’s important to note that in Nuevo León, much of this damage is attributed to indirect impacts, such as extreme precipitation. The discussion emphasizes that cyclone intensity by itself, is not the reason for the damage magnitude, as factors like precipitation levels, and regional vulnerability are crucial drivers.